2007
DOI: 10.1211/jpp.59.4.0007
|View full text |Cite
|
Sign up to set email alerts
|

Amides from Piper nigrum L. with dissimilar effects on melanocyte proliferation in-vitro

Abstract: Melanocyte proliferation stimulants are of interest as potential treatments for the depigmentary skin disorder, vitiligo. Piper nigrum L. (Piperaceae) fruit (black pepper) water extract and its main alkaloid, piperine (1), promote melanocyte proliferation in-vitro. A crude chloroform extract of P. nigrum containing piperine was more stimulatory than an equivalent concentration of the pure compound, suggesting the presence of other active components. Piperine (1), guineensine (2), pipericide (3), N-feruloyltyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
29
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
5
29
0
3
Order By: Relevance
“…Previous studies have revealed that compounds isolated from plants of the genus Piper had potent anticancer properties (13,(21)(22)(23)(24). The results of the present study illustrated that the PFPE had anticancer and cancer preventive effects on mammary tumorigenesis in rats.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Previous studies have revealed that compounds isolated from plants of the genus Piper had potent anticancer properties (13,(21)(22)(23)(24). The results of the present study illustrated that the PFPE had anticancer and cancer preventive effects on mammary tumorigenesis in rats.…”
Section: Discussionsupporting
confidence: 68%
“…The pepper alkaloids are also present in the dried fruits of P. nigrum, piperine, and piplartine and have exhibited cytotoxic effects on HL-60, CEM, HCT-8, and B-16 cell lines (23). In addition, P. nigrum and its derivative extracts have been reported to inhibit tumor growth in vitro and in vivo (13,16,24). While screening for cytotoxic effects of plants of the genus Piper in our previous study, we found that the recrystallized extract of P. nigrum that was piperine free had a potent cytotoxic activity on breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Extracts of P. longum have been demonstrated to exert various properties, such as immunomodulatory effects, as well as hepatoprotective and antiasthmatic activity (20). It has been reported that PLM inhibits platelet aggregation (21), atherosclerosis plaque formation (22), and tumor cell growth (23,24). Interestingly, a recent report indicates that PLM can selectively kill tumor cells through increasing ROS levels (25).…”
mentioning
confidence: 99%
“…It also possesses radioprotective effects (Aggarwal & Kaul, 1992). Piperlongumine (2) is reported for killing of cancer cells by a small molecule targeting the stress response to ROS (Raj et al, 2011), antiplatelet (Lee et al, 2010), melanocyte stimulatory activity (Lin et al, 2007). It also acts as an antiaflatoxin agent (Lee et al, 2002).…”
Section: Introductionmentioning
confidence: 99%